Etude De La Contamination Par Les Métaux Lourds Des Eaux Et Des Sédiments Au Voisinage De La Mine De Tighza (Maroc Central Oriental) - Farah El Hassani; Abdellah Boushaba; Noureddine Raïs; Lahcen Benaabidate (European Scientific Journal, ESJ, 2016)
The analyses performed on four stations upstream and eight downstream of the Tighzamine (Jebel Aouam) were carried out to assess the contamination degree from tailings discharges. From the standpoint of water and soil qualities, concentrations of trace and major elements (TME), including Cd, Mn, Pb and Zn which concentrations (µgL-1 ) reach respectively 82, 49918, 669, 36858 in water samples and 443, 161, 23607, 19459 in sediments, exceed greatly, in the vicinity of the mine, the international standards. Depending on the TME analyzes, all downstream stations shows different degrees of contamination, whereas it is less or absent at the upstream stations. Downstream stations thus require water and soil treatment, since the contents TME are quite large and clearly present a danger not only in the surrounding environment for population, fauna and flora, but also over long distances especially as the waters of Tighza river flow into the oued Bouregreg and thus reach the Sidi Mohammed ben Abdellah Dam (Rabat) which is used as drinking water for urban consumption. It is therefore imperative to treat these waters, so that they become drinkable and avoid bad impacts to the population.